2016
DOI: 10.1158/0008-5472.can-16-1308
|View full text |Cite
|
Sign up to set email alerts
|

Trametinib Drives T-cell–Dependent Control of KRAS-Mutated Tumors by Inhibiting Pathological Myelopoiesis

Abstract: Targeted therapies elicit seemingly paradoxical and poorly understood effects on tumor immunity. Here we show that the MEK inhibitor trametinib abrogates cytokine-driven expansion of monocytic myeloid-derived suppressor cells (mMDSC) from human or mouse myeloid progenitors. MEK inhibition also reduced the production of the mMDSC chemotactic factor osteopontin by tumor cells. Together these effects reduced mMDSC accumulation in tumor-bearing hosts, limiting the outgrowth of K-Ras-driven breast tumors, even thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…In this case, PD-L1 increased expression was associated with immune evasion, indicating that KRAS mutant cancers could indeed benefit from treatment with anti-PD-L1 or anti-PD-1 immune checkpoint inhibitors. Interestingly, some works have already demonstrated that despite the lack of clinical relevance of MEK inhibitors when used as single agents, their combination with immunotherapies can result in increased clinical benefit [49][50][51][52]. These works claimed an effect of MEK inhibitors on the modulation of the immune-suppressive microenvironment that synergized with anti-PD-L1 or anti-CTLA-4 therapies to enhance treatment response [49,52].…”
Section: Targeting Mutant Kras-driven Effects That Shape the Cancer-imentioning
confidence: 99%
“…In this case, PD-L1 increased expression was associated with immune evasion, indicating that KRAS mutant cancers could indeed benefit from treatment with anti-PD-L1 or anti-PD-1 immune checkpoint inhibitors. Interestingly, some works have already demonstrated that despite the lack of clinical relevance of MEK inhibitors when used as single agents, their combination with immunotherapies can result in increased clinical benefit [49][50][51][52]. These works claimed an effect of MEK inhibitors on the modulation of the immune-suppressive microenvironment that synergized with anti-PD-L1 or anti-CTLA-4 therapies to enhance treatment response [49,52].…”
Section: Targeting Mutant Kras-driven Effects That Shape the Cancer-imentioning
confidence: 99%
“…For example, it has been proposed that cell death induced by anti-cancer therapy can release tumor antigen, leading to increased T cell functions 21,56 Indeed, it has been shown that MEK inhibition modulates the tumor microenvironment through mechanisms such as pathological myelopoiesis. 57 The effects of MEK inhibitor on T cell functions are also related to tested parameters of T cell functions. We found that MEK inhibitor does not alter expression of Granzyme B in T cells, whereas it inhibits all other tested parameters of T cell functions in this study.…”
Section: E1512456-10mentioning
confidence: 99%
“…In fact, in a KRAS-inducible breast cancer model, MEK inhibition prevented tumor progression in vivo through an immune-mediated mechanism, rather than by direct inhibition of tumor-cell proliferation. This mechanism, which required CD8 T cells, was mediated by the blockade of monocytic myeloid-derived suppressive cell (mMDSC) expansion [110]. Moreover, MEK inhibition increases the number of CD4 TILs and did not negatively affect the density of CD8 TILs in a fully competent colon carcinoma syngeneic mouse model [111].…”
Section: Mek Inhibitionmentioning
confidence: 99%